ANALISIS AKSESIBILITAS PETANI PERKOTAAN TERHADAP AGROINPUT DAN IMPLIKASINYA TERHADAP PENGEMBANGAN URBAN FARMING - Harniati Harniati; Reni Suryanti (Jurnal Penyuluhan Pertanian, 2021)
Urban Farming is growing rapidly and becoming as a part of the solution for food insecurityand malnutrition problems of urban citizen. But, the facilitation and development of urbanfarming have not been able to overcome problems and pressure faced by urban farmers mainlyaccessibility to agroinput yet. Objectives of this research were to 1) identify the problems ofagroinput, 2) to know accessibility of farmer to agroinput, 3) to analyze the policy implicationto the development of urban farming. The research used an explanatory survey method.Sampling method used waspurposive stratified random sampling. Availability of agroinput andfarmer’s accessibility were quantified using Likert’s Scale. Respondents were member offarmer’s group of paddy agribusiness, sheep, and processing of agriculture products. Thisresearch was conducted in the villages of Situ Gede and Margajaya for intra-urban, and PasirBuncir and Pasir Eurih of Tamansari for peri-urban.The observed variables are land, water,seeds/seedlings, fertilizers, pesticides, technologyas well as labor.Results of the study:1)agroinput that are difficult to access by farmers are land, labor, feed concentrate, fertilizer, andseed.Paddy land ownership in peri-urban is less than 0.2 Ha and in intra-urban areas are landlessfarmers. Outside labor is difficult to access because of itslimited amount or availibility and thewages is relatively expensive. Feed concentrate for sheep rarely available and not affordablebecause it’s expensive. Limited accessibility to agroinput for urban agribusiness and itsproblems and challenge will bring changing policy implication for developing urban farming,mainly for facilitation, development of urban agribusiness model, empowering institusional, andregulatory.